2016
DOI: 10.1016/j.pmedr.2016.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Current cigarette smoking is a reversible cause of elevated white blood cell count: Cross-sectional and longitudinal studies

Abstract: While cigarette smoking is a well-recognized cause of elevated white blood cell (WBC) count, studies on longitudinal effect of smoking cessation on WBC count are limited. We attempted to determine causal relationships between smoking and elevated WBC count by retrospective cross-sectional study consisting of 37,972 healthy Japanese adults who had a health check-up between April 1, 2008 and March 31, 2009 and longitudinal study involving 1730 current smokers who had more than four consecutive annual health chec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
61
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 28 publications
14
61
2
1
Order By: Relevance
“…In terms of inflammation, total inflammatory cell counts in gingival samples of smoker periodontitis patients were significantly higher than smoker healthy, healthy and non‐smoker periodontitis patients. Increased inflammatory cell counts found in the present study are compatible with the results of previous studies . Regarding HIF‐1α expressions, periodontitis patients and healthy volunteers exhibited similarly lower values compared with the equivalent smoker groups.…”
Section: Discussionsupporting
confidence: 92%
“…In terms of inflammation, total inflammatory cell counts in gingival samples of smoker periodontitis patients were significantly higher than smoker healthy, healthy and non‐smoker periodontitis patients. Increased inflammatory cell counts found in the present study are compatible with the results of previous studies . Regarding HIF‐1α expressions, periodontitis patients and healthy volunteers exhibited similarly lower values compared with the equivalent smoker groups.…”
Section: Discussionsupporting
confidence: 92%
“…The results showed a significantly high in eosinophil (EOS) and no significant in neutrophil (NEU), while there was a significantly low in monocyte (MON) and no significantly in lymphocyte (LYM). This result consistent with (Higuchi et al, 2016) where noted increased total leukocyte count observed in smokers. Also the result show no significantly high in RBC, significantly high in Hb and PLT and no significantly low in PCV, MCV, MCH and MCHC Table (1)these result consistent with (Malenica et al, 2017) where noted increased total leukocyte count observed in smokers.…”
Section: Resultssupporting
confidence: 91%
“…for elevated FeNO, and keeping the same cut‐off for B‐Eos (300 cells/μL) did in fact for the intermediate FeNO cut‐off lead to significant correlations between simultaneously elevated markers and most symptoms and attacks (data not shown) possibly indicating that a higher cut‐off for FeNO would be more appropriate. B‐Eos levels are also reported to vary with age, with increasing levels after 30‐40 years of age, and to be affected by smoking, where B‐Eos levels are increased in smoking subjects in a general population, but seem to decrease in asthmatic individuals who smoke . For B‐Eos, the changes in relation with asthma morbidity by increasing cut‐offs from 300 to 400 and 500 cells/μL increased slightly in this material.…”
Section: Discussionmentioning
confidence: 67%